Physiological profile evaluation through lactate and heart rate In national level Greco-Roman wrestlers - Pilianidis, T.; Barbas, I.; Mantzouranis, N.; Kasabalis, A.; Mantis, K.; Mirzaei, B. (International Journal of Wrestling Science, 2011)
The purpose of this study was to evaluate the physiological profile of top-level wrestlers in a simulated competition. 12 male athletes, aged 23.2±4.5yrs who were participants in the 74kg division at the Greece National Greco-Roman Championship were the evaluated subjects. During all competitions the heart rates were measured and stored with a transmitter with a digital display while the capillary blood samples were collected 3 minutes after each round was completed in order to evaluate the lactate concentrations. The statistical design was based on the One-Sample T-Test analysis. The statistics showed that the mean-max heart rate values (b·min-1) and mean-max lactate concentrations (mmol·l-1) in 2nd and 3rd round were significantly higher than in the 1st round. Specifically, the values were as follows: 1st round HRmean 138±4 - HRmax 143; Lamean 12.43±2.8 - Lamax 15.80, 2nd round HRmean 172.2±5.6 - HRmax 178; Lamean 13.67±2.7 - Lamax 19.3, 3rd round HRmean 183±6.3 - HRmax 193; Lamean14.6±2.7 - Lamax 20.26. The results indicate that the physiological profile of these wrestlers was both aerobic and anaerobic. Conclusively, the wrestling aerobic training with a simultaneously increase in anaerobic threshold could contribute to a benefit in tactical especially in the last round of a Greco-Roman wrestling competition.